“THE DECLINE OF NATION” – ALIENATION FROM SOCIETY, VIRTUALIZATION, “I” CONCEPT, NEW METHODS AND MECHANISMS OF PROMOTING IDEAS OF LGBT INTO THE MINDS OF YOUTH - Nigora Xusanova (Journals Park Publishing, 2023)
In the article, the qualities and feelings of a person are considered as universal values, moreover, the decline of nationality fell on the influence of “Mass Culture”, a new approach to understanding the personality of a person – “I -concepts”, deviant behavior, cybercrime, drug epidemic, human trafficking, LGBT, suicide problems. In addition, the most painful moments of modern society are presented - the loss of spiritual values, such as a single homeland, family, children, faith, kindness among people.
Keywords: Nationalism, crisis, threat, alienation in society, virtualization, “Concept of I”, childlessness, conflict of beliefs, deviant behavior, LGBT, “Zed generation”, “Instastars”, “instaalpha, instamale, “instafemale”, “memes”, “challenge”, “Satan”, “Satanist”, “popit and antistress”, “Redan movemen”.